Perspectives and Importance of Social Sports in Women with Experiences of Gender Violence - Theran , Kelly Mercedes Diaz; Contreras , Blanca Flor Pérez; Santamaría-Campo, Susan Karola; Carazo , Rosana Martínez; Salcedo , Carmen Aleida Cadrazco; Marín , Joseimar Garrido (Journal of Ecohumanism, 2024)
This study aims to analyze the perspectives and importance of social sport in women with experiences of gender violence, understanding the role of sport in the process of empowerment and self-improvement from gender and feminist theories, which highlights sport as a space of resistance and social transformation for women. The methodology was quantitative approach, descriptive in scope to a sample of 163 women victims of violence who have used sport to face their recovery process, quantitative analyses were used using IBM SPSS and R-Project 4.2.3, for the analysis of the data began with analysis of measures of central tendency. In addition, a CLUSTER analysis was used to expose the inferential results, using interview and questionnaires as data collection techniques. The results revealed that sport not only helps women to improve their self-esteem, but also to rebuild support networks and strengthen their resilience. In conclusion, social sport emerges as a tool to overcome violence and build stronger and more secure identities, demonstrating that, when carried out in a supportive environment, it can have a lasting impact on women’s lives.